Changes in Doppler echocardiography depending on type of elite athletes immediately after maximal exercise - Park, S.; Moon, Y. J.; Nam, G. B.; Kim, Y. J. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: This study explores physiologic differences in the cardiac structure and function of elite athletes during the resting state and immediately after maximum exercise by training type compared to healthy controls. METHODS: The study focuses on elite middle-long distance group (MLDG), weightlifter group (WG), and a control group (CG). Cardiac structure, systolic function, and diastolic function were measured for all subjects at resting state and immediately after maximum exercise using echocardiography. RESULTS: During the resting state, the athlete groups had significantly larger inter-ventricular septum thickness end diastolic (IVSd) and inter-ventricular septum thickness end systolic (IVSs); the left ventricular posterior wall thickness end-diastolic (LVPWd) in MLDG was significantly larger than the CG. Moreover, the athlete groups had significantly higher left ventricular internal dimension end-diastolic (LVIDd), left ventricular internal dimension end-systolic (LVIDs), left ventricular mass (LVM), LVM index, left ventricular end-diastolic volume (LVEDV), left ventricular end-systolic volume (LVESV), and left ventricular fraction shortening (LVFS) compared to the CG. Also, the MLDG had higher LVIDd, LVIDs, LVM, LVM-index, LVEDV, LVESV than the WG. The LVSV and LVSV index in MLDG were significantly higher than the CG and WG. The LVEF of CG was significantly higher than the athlete groups. Immediately following the maximum exercise test, MLDG had a significantly higher LVEDV, LVSV, LVSV-index, LVCO, LVCO index, E/A and DT than WG and CG. CONCLUSIONS: The MLDG showed high LVCO with comparatively better compliance in left ventricular diastolic function following maximum exercise, with a low heart rate as consequence of good LV contractility due their excellent LV diastolic function.